Design Of The Information System Model For Kodim 1416/Muna Administration Process Using The RAD Method With Whatsapp Based Notification - Ruslan, Fisabilia Adipati; Wahyu, Sawali (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2024)
Globalization, driven by advancements in information technology, demands fundamental changes across various life aspects, including the operations of companies and organizations. Kodim 1416/Muna faces issues in daily reporting and administration due to reliance on WhatsApp, varying report formats, and delays in administrative approvals. This research aims to design an information system model to address these problems using the Rapid Application Development (RAD) method, encompassing requirements planning, design, and implementation. The designed system is expected to standardize daily reports, reduce the risk of overlooked information, expedite the submission process, and facilitate monitoring by leaders through WhatsApp notifications. System Usability Scale (SUS) testing results show a score of 81, categorized as "Good Performance," indicating user satisfaction with the designed system. Thus, this research contributes to improving operational efficiency and administrative performance at Kodim 1416/Muna.